Investigation of the Thermal Performance of Water and Aluminum Oxide Nanofluid as a Coolant for Solar Panels - Farhan A.F.I.A.; Aziz N.A.M.; Mohamed H.; Zainal B.S.; Junoh H. (Semarak Ilmu Publishing, 2024)
A solar panel, also known as a photovoltaic (PV) panel, converts photons from sunlight into usable energy. However, panel warming during the day limits voltage production and results in energy-electricity waste. The efficiency of this PV panel's cooling system utilizing water and aluminum oxide (Al2O3) nanofluid was simulated and assessed using Computational Fluid Dynamics (CFD). This research examines the thermal performance of temperature differences between uncooled, water-cooled, and Al2O3 nanofluid-cooled solar panels. To find the lowest temperature of the solar panel achieved, the mass flow rates of coolants (16.5, 33, 66, and 99 L/h) and inlet coolant temperatures (20, 25, 30, 35, and 40 C) were varied. Al2O3 nanofluid-cooled solar panels at the maximum flow rate and the lowest inlet coolant temperature, 99 L/h and 20?, respectively, promised the minimum solar panel temperature, which is critical for energy storage. Furthermore, the use of nanofluid coolant assisted in the reduction of 41 to 60% of solar panel temperature. These results shed insight into the capabilities of nanofluid in the coolant system. 2023, Semarak Ilmu Publishing. All rights reserved.